The Influence of Self-efficacy on Organizational Commitment and Ethical Behavior: The Role of Job Satisfaction - Ana Sofia Aryati; Armanu (Jurnal Manajemen Teori dan Terapan, 2023)
Objective: This study aims to analyze the effect of self-efficacy on organizational commitment and ethical behavior. Furthermore, this study also examines the mediating role of job satisfaction in determining the relationships.